ASPEK PAJAK PERTAMBAHAN NILAI PADA BIRO PERJALANAN WISATA (STUDI KASUS PT V) - elsie kasim; Fildza Virginia (Universitas Indonesia, 2019)
This study discusses the aspects of Value Added Tax on travel bureau (case study of PT V). Data collection techniques used in this study is literature studies (Library Research) and field studies (Field Research). The results of research and analysis can be concluded as follows The amount of tax base for submission which includes brokerage and/or agency services is replacement, amounting to 100% of the total cost. The amount of tax base of services that do not include brokerage services and/or agency using other values as the basis for the tax is 10%. Obstacles is the limitation of insight and understanding of the opposing party's transactions concerning taxation on the travel bureau.Key words: Value Added Tax, Travel Bureau, Case Study